Karakteristik Kebijakan Pemerintah Kecamatan Sungai Gelam Kabupaten Muaro Jambi - Irwandi; Ratnadewi; Andrizal (Jurnal Hukum Respublica, 2018)
This study aims to explain the characteristics of government policies in Sungai Gelam District, Muaro Jambi Regency. The research method used is empirical juridical and the procedure for sampling is done by purposive sampling. The results showed that. The role of the camat in the fostering and supervision of village administration in Sungai Gelam Sub-district is based on Article 21 of Government Regulation No. 19/2008 concerning Kecamatan. The sub-district government has a strategy in fostering and overseeing village administration through the mapping of regions or villages that are experiencing difficulties in administering village government administration. Basically, the sub-district government has provided guidance and supervision to the village government, but the details are not included in the work program. This was proven in every 6 months the village government was asked to evaluate the performance so that there were no mistakes. Then always fostering village officials with a pattern when village officials have problems in the field always consult with the head of government. Camat supervision and supervision programs always carry out evaluations in matters of village government administration. So, the implementation of the program is not detailed, but carried out in accordance with the needs that exist in the village government. One of the obstacles to the guidance and supervision of village administration is to improve the ability and inadequate human resources and the lack of staff who have expertise.